The Effectiveness of Intertribute Stereotypes Viewed from Individual Counseling Rational Emotif and Cognitive Behavioral Therapy Approach in SMA Swasta Puteri Sion Medan - Nuraini Nuraini; Mina Sari Silitonga; Desi Sepriani (Budapest International Research and Critics University, 2020)
This study aims to determine the effectiveness of individual counseling services with an emotive rational approach and cognitive behavioral therapy in minimizing inter-ethnic stereotypes in SMA Swasta Puteri Sion Medan. The type of research used isdescriptive qualitative. The subjects in this study were 8 students of Puteri Sion Medan Private High School who had high inter-ethnic stereotypes. Data collection methods used are observation, interviews, and scale. To analyze the data using descriptive qualitative data analysis and percentage descriptive data analysis. The results of this study indicate that in the pre-test the average score of inter-ethnic stereotypes was 60 or 43% in the high category, while the post-test score obtained an average score of 126 or 90% in the low category. There was a change in inter-ethnic stereotypes in students from the high category to the low category. This means that inter-ethnic stereotypes can be minimized through individual counseling with an emotive rational approach and a cognitive behavioral therapy approach to SMA Swasta Puteri Sion Medan.